Terapi Mindfulness untuk Meningkatkan Adaptasi Diri dan Mengurangi Gangguan Psikologis pada Keluarga dengan ODGJ - Anindyarani Fitri; Meidiana Dwidiyanti; Dian R. Sawitri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the impact of mindfulness on the families of patients with mental disorders. The method used in this study was a literature review. Articles were collected using the ScienceDirect, Scopus, and Garuda databases with mindfulness, caregiver, family, and mental illness. The inclusion criteria included articles published from 2018-2022. The study results in show that mindfulness interventions reduce stress and the burden on family life and improve quality of life, family acceptance, and coping in families who care for patients with mental disorders. Mindfulness intervention is a therapy used to regulate individual emotions to accept the unpleasant events they experience. In conclusion, mindfulness interventions can be a solution for dealing with families with physical and mental health problems caused by living with mentally ill patients. Keywords: Mental disorders, Family, Mindfulness, Caregivers